Causes and Consequences of Interdialytic weight gain - Karin J.R. Ipema; Johanna Kuipers; Ralf Westerhuis; Carlo A.J.M. Gaillard; Cees P. van der Schans; Wim P. Krijnen; Casper F.M. Franssen (Karger Publishers, 2016)
Background/Aims: Higher interdialytic weight gain (IDWG) is associated with higher predialysis blood pressure and increased mortality. IDWG is also increasingly being recognized as an indicator of nutritional status. We studied in detail the associations of various patient factors and nutritional parameters with IDWG. Methods: We collected data during one week for IDWG and hemodynamic parameters in 138 prevalent adult haemodialysis patients on a thrice-weekly haemodialysis schedule. A multivariate linear regression analysis was employed to identify factors that are associated with IDWG. Results: The mean (±SD) age was 62.5 (±18.2) years, 36% were female, 36% had diuresis, and 23% had diabetes. Patients in the highest IDWG tertile were significantly younger, more frequently male, and had a significantly higher subjective global assessment score (SGA). A higher IDWG as a percentage of body weight (%IDWG) was associated with a younger age, greater height and weight, absence of diuresis, and lower postdialysis plasma sodium levels. The model with these five parameters explained 37% of the variance of %IDWG. Predialysis, intradialysis, and postdialysis diastolic blood pressure was significantly higher in the highest tertile of IDWG. Conclusion: The most important associations of %IDWG are age, height, weight, diuresis, and postdialysis sodium. Patients with the highest IDWG have significantly higher diastolic blood pressures.